2022
DOI: 10.24275/rmiq/bio2824
|View full text |Cite
|
Sign up to set email alerts
|

Selenium accumulation by Lactobacillus isolated from commercial fermented milk: minimum inhibitory concentration and kinetic growth changes

Abstract: totales del petróleo intemperizados en suelos y sedimentos (Biodegradation modeling of sludge bioreactors of total petroleum hydrocarbons weathering in soil and sediments)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…These kinetic parameters are intended to somehow explain the metabolic behavior of microorganisms according to the environment in which they are found. Castañeda-Ovando et al [16] related the growth of lactic bacteria in monoculture and co-culture to determine the fundamental differences in the process. Thus, the two main metabolic identification parameters are proteolytic capacity and lactic acid production.…”
Section: Microbial Growth and Lactic Acid Productionmentioning
confidence: 99%
See 2 more Smart Citations
“…These kinetic parameters are intended to somehow explain the metabolic behavior of microorganisms according to the environment in which they are found. Castañeda-Ovando et al [16] related the growth of lactic bacteria in monoculture and co-culture to determine the fundamental differences in the process. Thus, the two main metabolic identification parameters are proteolytic capacity and lactic acid production.…”
Section: Microbial Growth and Lactic Acid Productionmentioning
confidence: 99%
“…It has been reported that in lactic acid bacteria, proteolytic activity and protein hydrolysis patterns vary considerably between strains [15,16]. These differences could be due to multiple factors, among which the following have been pointed out: (1) changes and mutations in the genes involved in the proteinase expression linked to the cell wall, and (2) the conditions in which the enzymatic activity is carried out [17].…”
Section: Free Amino Groups Analysis By Tnbsmentioning
confidence: 99%
See 1 more Smart Citation